« Amitiés vives » Littérature et amitié dans les correspondances d'écrivains - Battiston, Régine; Dziub, Nikol; VOEGELE, Augustin (EPURE, Éditions et presses universitaires de Reims, 2022)
What is special about friendship as it develops in writers' letters from the Romantic period onwards? If writers' friendly correspondence is not just literature, what are the specific features of writers' epistolary friendships? What kind of friendship is revealed in the letters exchanged between letter-writers?